Electronic Module Development on Algebra Structure Courses - Agustina, Olympia; Farida, Farida; Putra, Fredi Ganda (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to describe the process of developing an electronic module in the algebraic structure course, and knowing the effectiveness of the electronic module after being tested on mathematics education students. This research was conducted in class C, 5th semester, majoring in mathematics education at UIN Raden Intan Lampung. The development model used in this research is the Borg and Gall development model. The development of the electronic module was carried out based on the Articulate Studio'13 application. The types of data taken in this study were qualitative data and quantitative data. From the results of due diligence from experts and student responses, the results of the development of an electronic module are very feasible and very interesting. Then, based on the results of the final assessment of student’s effectiveness of the product showed a presentation of more than 75%. Based on the research results, it can be concluded that the electronic module in the algebraic structure course is effectively used by mathematics education students.